Characterization of a Mixed-Valence Ru(II)/Ru(III) Ion-Pair Complex. Unexpected High-Frequency Electron Paramagnetic Resonance Evidence for Ru(III)-Ru(III) Dimer Coupling - Impert, Olga; Kozakiewicz, Anna; Wrzeszcz, Grzegorz; Katafias, Anna; Bieńko, Alina; van Eldik, Rudi; Ozarowski, Andrew (Inorganic Chemistry, 2020)
In this contribution, we report the synthesis and full characterization of the first mixed-valence Ru(II)/Ru(III) ion-pair complex, [RuII(bipy)2(pic)]+[cis-RuIIICl2(pic)2]-, in the solid state and in aqueous solution, where bipy = 2,2′-bipyridine and pic- = picolinate. In addition, unexpected high-frequency electron paramagnetic resonance evidence for interactions between two neighboring Ru(III) ions, resulting in a triplet state, S = 1, was found.
CRIS-Team Scopus Importer:2020-06-09